Low Power Laser Applications in Pediatric Dentistry: Review Article - Angeles Maslucan, Romy Janet (2021)
Aim: to identify and systematize information of greater relevance in the use of Low Power Lasers (LLLT) in various pediatric dentistry treatments. Methodology: Electronic databases (Medline, Scielo, Scopus, Pubmed, Elsevier and other non-indexed citations) were reviewed, from January 2014 to December 2020. Papers written in English, Portuguese and Spanish, full text available using the keywords: Low power laser, pediatric dentistry laser and photobiomodulation. A total of 65 articles were obtained which were analyzed and selected by a master expert in laser therapy, 46 articles were accepted. Results: The application of the low power laser constitutes a tool for the diagnosis of dental caries. In addition, it allows the resolution of signs and symptoms in oral pathologies. In pulp therapies, success rates greater than 95% are shown. Photobiomodulation in pediatric patients is effective as a preventive to chemotherapy treatment. The application of a low-power laser with methylene blue reduces the total of Streptococcus mutans. The combination of low-power laser and varnish has a good desensitizing action on teeth with MIH, it is effective in reducing pain at the TMJ level in children. Conclusions: The low-power laser is a therapeutic alternative in pediatric patients, showing rapid control of inflammation, pain, accelerating cellular repair processes and it is silent. It is effective in the diagnosis of enamel caries (DIAGNOdent) and dentin (CarieScan pro).